Temperature Field Variation Law of Low Exothermic Polymer Grouting Material in Repairing Void Damage of Frozen Soil Subgrade - Bei Zhang; Baolin Wang; Yanhui Zhong; Shuangjie Wang; Xiaolong Li; Shilun Wang (Advances in Materials Science and Engineering)
In this study, the self-developed grouting mold was used to study the heat release characteristics of different density polymer grouting material under different temperature conditions. The spatial distribution characteristics of the frozen soil subgrade temperature field under the effect of polymer grouting repair were analyzed. Further, the rules governing the temperature change of a frozen soil subgrade monitoring point under the effect of polymer grouting repair were studied. The heat transfer mechanism of polymer grouting material in frozen soil subgrade was revealed. The results showed that in the void region of the frozen soil subgrade, a discontinuity zone appeared in the temperature field distribution isotherm due to the effect of voids; this zone exhibited a layered radioactive distribution along the two sides of the void area. Furthermore, during the exothermic stage of the curing reaction, the temperature distribution isotherms changed from a layered radioactive distribution to a ring distribution that decreased from the inside to outside. During the natural cooling process, the peripheral temperature of the ring isotherm first decreased and a negative temperature ring-shaped isotherm gradually formed. Finally, the upper boundary of the influence of the heat energy released by the curing reaction on the frozen soil subgrade temperature field was determined to be 30 cm, and the lower boundary was 20 cm.